ANALISIS HUBUNGAN INDEKS HARGA SAHAM DOMESTIK, INDEKS HARGA SAHAM INTERNASIONAL, DAN KURS: PENDEKATAN VECTOR AUTOREGRESSION (VAR) - A. J. Ibnu Wibowo (Center for Economic Studies Universitas Katolik Parahyangan, 2011)
This research aims to analyze the relation between domestic share price index variable (composite share price index), international share indexes, and Rp/US exchange rate simultaneously. This research uses weekly data along August 2007-April 2008 period. The data is then analyzed with vector autoregression method (VAR). The result of analysis with impulse response function shows that IHSG variable tends to give positive response towards shock of exchange rate variable, Dow Jones Index, Hangseng Index, Singapore Index, or Nikkei Index. Meanwhile, the analysis of variance decomposition shows that along 10 observations periods, /HSG variable tends to give the biggest average contribution (49%-100%) towards the movement of /HSG variable, while Singapore's index variable gives the smallest average contribution (0%-2,9%).